Changes in blood lipids and blood pressure during adolescence. Issue 6231 (28th June 1980) - Orchard, T J; Rodgers, M; Hedley, A J; Mitchell, J R
Abstract : A total of 625 adolescents from three general practices participated in a cross-sectional study of cardiovascular disease risk factors. The girls had higher serum total and high density lipoprotein (HDL) cholesterol concentrations than the boys, while the boys had higher serum triglyceride concentrations. Smoking (equally prevalent in both sexes) was associated with lower HDL cholesterol concentrations, particularly in boys, while in girls use of oral contraceptives was associated with higher total cholesterol and lower HDL cholesterol concentrations showed striking associations with age, height, and sexual maturation in boys, but not in girls. Triglyceride concentrations were associated with age in boys. Systolic blood pressure and serum urate concentrations were higher in boys and rose steeply with age, but no age association was seen for urate concentrations or systolic blood pressure in girls or for diastolic pressures in either sex. Girls, however, had higher diastolic pressures. There was a strong association between urate concentration and the other cardiovascular disease risk factors, especially HDL cholesterol. Adolescence is associated with considerable changes in cardiovascular disease risk factors, and there are striking sex differences in these changes.